Exploring the History and Characteristics of Political Rhetoric - Saidova Fazilatmo Saidamirovna (IJLHE: International Journal of Language, Humanities, and Education, 2022)
In this article, the author provides a comprehensive analysis of the history and characteristics of political rhetoric. The origin and specific belonging of political rhetoric are explored in depth, along with an examination of its various forms and components. One important aspect highlighted in this article is the influence of rhetorical ideas on the foundations of ordinary people's thinking. The author emphasizes the significant role of rhetoric in the restructuring of the political and social sphere, particularly in shaping democratic values. The paper further highlights the importance of rhetoric in the development of democratic societies. By examining the ways in which political rhetoric has been used throughout history to influence public opinion and promote democratic ideals, the author demonstrates its crucial role in shaping the political landscape. Overall, this article presents a thorough and insightful exploration of the history and significance of political rhetoric, shedding light on its key features and its impact on democratic societies.